Mitochondrial targets for volatile anesthetics against cardiac ischemia-reperfusion injury - Agarwal, Bhawana; Stowe, David F.; Dash, Ranjan K.; Bosnjak, Zeljko J.; Camara, Amadou K. S. (Frontiers in Physiology, 2014)
Mitochondria are critical modulators of cell function and are increasingly recognized as proximal sensors and effectors that ultimately determine the balance between cell survival and cell death. Volatile anesthetics (VA) are long known for their cardioprotective effects, as demonstrated by improved mitochondrial and cellular functions, and by reduced necrotic and apoptotic cell death during cardiac ischemia and reperfusion (IR) injury. The molecular mechanisms by which VA impart cardioprotection are still poorly understood. Because of the emerging role of mitochondria as therapeutic targets in diseases, including ischemic heart disease, it is important to know if VA induced cytoprotective mechanisms are mediated at the mitochondrial level. In recent years, considerable evidence points to direct effects of VA on mitochondrial channel/transporter protein functions and electron transport chain (ETC) complexes as potential targets in mediating cardio-protection. This review furnishes an integrated overview of targets that VA impart on mitochon-drial channels/transporters and ETC proteins that could provide a basis for cation regulation and homeostasis, mitochondrial bioenergetics, and reactive oxygen species (ROS) emission in redox signaling for cardiac cell protection during IR injury.